Study on influences of TiN capping layer on time-dependent dielectric breakdown characteristic of ultra-thin EOT high-k metal gate NMOSFET with kMC TDDB simulations - 徐昊 杨红 罗维春 徐烨峰 王艳蓉 唐波 王文武 祁路伟 李俊峰 闫江 朱慧珑 赵超 陈大鹏 叶甜春 (Chinese physics B, 2016)
The thickness effect of the TiN capping layer on the time dependent dielectric breakdown（TDDB） characteristic of ultra-thin EOT high-k metal gate NMOSFET is investigated in this paper.Based on experimental results,it is found that the device with a thicker TiN layer has a more promising reliability characteristic than that with a thinner TiN layer.From the charge pumping measurement and secondary ion mass spectroscopy（SIMS） analysis,it is indicated that the sample with the thicker TiN layer introduces more Cl passivation at the IL/Si interface and exhibits a lower interface trap density.In addition,the influences of interface and bulk trap density ratio Nit/Not are studied by TDDB simulations through combining percolation theory and the kinetic Monte Carlo（kMC） method.The lifetime reduction and Weibull slope lowering are explained by interface trap effects for TiN capping layers with different thicknesses.